2017
DOI: 10.1515/biolog-2017-0109
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and biochar with N-fertilizer affect soil N2O emission in Haplic Luvisol

Abstract: The benefits of biochar application are well described in tropical soils, however there is a dearth of information on its effects in agricultural temperate soils. An interesting and little explored interaction may occur in an intensive agriculture setting; biochar addition may modify the effect of commonplace N-fertilization. We conducted a field experiment to study the effects of biochar application at the rate of 0, 10 and 20 t ha

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Castaldi et al, 2011;Cornelissen et al, 2018). Since the biochar is alkaline, it might increase of soil pH, but this effect could be softened with adding The biochar application can be beneficial for soil pH enhancement (e. g. Chintala et al, 2013;Obia et al, 2015;Horák et al, 2017;Teutscherova et al, 2017;Šimanský et al, 2018) as confirmed by our data. As shown in Fig.…”
Section: Tablesupporting
confidence: 80%
“…Castaldi et al, 2011;Cornelissen et al, 2018). Since the biochar is alkaline, it might increase of soil pH, but this effect could be softened with adding The biochar application can be beneficial for soil pH enhancement (e. g. Chintala et al, 2013;Obia et al, 2015;Horák et al, 2017;Teutscherova et al, 2017;Šimanský et al, 2018) as confirmed by our data. As shown in Fig.…”
Section: Tablesupporting
confidence: 80%
“…Significantly lower N 2 O emission peaks were recorded from soils with biochar application compared to those without biochar, resulting in lower cumulative N 2 O emissions from biochar-amended soils during the first year of the experiment. Total cumulative N 2 O emissions (taken between March and November 2014) from the soil with biochar with or without N-fertilizer were 19-32% lower than those from the soil without biochar [42]. The results confirm that biochar application has the potential to reduce N 2 O emissions from the soil.…”
Section: Published Outputs From the Biochar Experiments In Slovakiamentioning
confidence: 54%
“…Factorial experiments are therefore one of the most effective ways of elucidating these relationships and interpreting in detail the impact of biochar on the particular crop. Early results from this experiment observed in 2014 could be indicative of a rapid change in soil properties, the highest barley yields were obtained in plots with pH of about 5.65 [42]. During the growing season a conventional digital camera was used as a non-destructive non-contact method of crop emergence monitoring and crop growth development [51].…”
Section: Published Outputs From the Biochar Experiments In Slovakiamentioning
confidence: 98%
“…This study aimed to determine and compare the long-term effect of the biochar-based organic amendments on selected soil properties (MBC, DHA and soil microbial community abundance) on the agricultural land of the temperate climate zone of Central Europe. Only a few studies have been done so far on the agricultural area of temperate soils [37][38][39]. Prior studies suggested that manure addition to biochar as a soil amendment might have a synergistic or antagonistic effect.…”
Section: Introductionmentioning
confidence: 99%